Pengaruh Matakuliah Ekonomi UMKM dan Kewirausahaan terhadap Minat Mahasiswa untuk Berwirausaha - Elmira Febri Darmayanti (Akuisisi: Jurnal Akuntansi, 2018)
The purpose of this study was to determine the effect Economics of UMKM and Entrepreneurship subjects on students' interest in entrepreneurship. This study used 151 Economics and Business Faculty (FEB) UM Metro students as respondents in filling out the questionnaire. Respondents are students who have obtained Economics of UMKM and Entrepreneurship courses. Data analysis in this study is included in quantitative research and intended to test hypotheses. Research analysis uses Structural Equation Modeling (SEM). The data collected is processed with the SmartPLS 3.0 program, and using non response bias tests, data quality tests, model tests, hypothesis testing, and variable descriptive analysis, so that a complete model of research results can be obtained. The results showed that there was a positive and significant influence from the Economics of UMKM and Entrepreneurship courses on the interest of FEB students in entrepreneurship. This shows that FEB UM Metro students have a high interest in entrepreneurship after gaining knowledge through UMKM Economics and Entrepreneurship courses.